1998
DOI: 10.1021/ja974192i
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Solid-State NMR Studies of Trichloroethylene Photocatalysis: Formation and Characterization of Surface-Bound Intermediates

Abstract: In situ solid-state NMR methodologies have been employed to investigate the photocatalytic oxidation of trichloroethylene (TCE) over two TiO2-based catalysts, Degussa P-25 powder and a monolayer TiO2 catalyst dispersed on porous Vycor glass. 13C magic angle spinning (MAS) experiments reveal that similar reaction intermediates form on the surfaces of both catalysts. Long-lived intermediates, including dichloroacetyl chloride (Cl2HCCOCl, DCAC), carbon monoxide, and pentachloroethane and final products CO2, phosg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 55 publications
3
73
0
1
Order By: Relevance
“…Solid state NMR has long been used to identify and characterize the structures of small organic molecules adsorbed onto catalytic surfaces [10][11][12], argon matrices [13], silica and alumina surfaces [14][15][16]. There similarly exist a number of solid state NMR pulse techniques capable in principle of reporting the structures of surface-adsorbed proteins.…”
Section: Nmr Methods For the Study Of Protein Structure At Biomateriamentioning
confidence: 99%
See 1 more Smart Citation
“…Solid state NMR has long been used to identify and characterize the structures of small organic molecules adsorbed onto catalytic surfaces [10][11][12], argon matrices [13], silica and alumina surfaces [14][15][16]. There similarly exist a number of solid state NMR pulse techniques capable in principle of reporting the structures of surface-adsorbed proteins.…”
Section: Nmr Methods For the Study Of Protein Structure At Biomateriamentioning
confidence: 99%
“…These models are derived from the full set of 1,000 models. Alignment of the models in the figure was based on root-mean-square deviation calculation of segments (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) and (33)(34)(35)(36)(37)(38) between the 8 models. Table 1 31 P-31 P nearest neighbor distances lying within a sphere of radius 6 Å for the 004 crystal plane in in monoclinic HAP.…”
Section: Figmentioning
confidence: 99%
“…The amount of DCAC adsorbed on Sample T was three times greater than the initial amount of TCE. It is reported that TiO 2 can adsorb DCAC to some extent [17][18][19]24,29]. The adsorption capacities of Samples M and C for DCAC are about four times greater than that of Sample T. Figure 3 shows the changes in the average degradation rate of TCE during the repeated runs using Samples T, M, and C. The degradation rate increased with the repeated run for all the samples.…”
Section: Photocatalytic Degradation Of Tcementioning
confidence: 97%
“…We have introduced a new approach, the use of in situ solid-state NMR (SSNMR) spectroscopy to the study of the surface chemistry of photocatalytic oxidation reactions. [7][8][9] The use of in situ SSNMR to study the near-UV light driven oxidation reactions yields an abundance of information about the reaction chemistry of organic molecules on the catalyst surface because of the atomic specificity, high resolution, and quantitative capabilities of NMR as well as its ability to distinguish between strongly or weakly bound or mobile species. In this paper, we use ethanol to probe the different electronic environments of a number of single and multiple monolayer metal oxide catalysts supported on porous Vycor glass.…”
Section: Introductionmentioning
confidence: 99%